THE EFFECT OF PROFITABILITY, LEVERAGE, SALES GROWTH, AND INVESTMENT OPPORTUNITY SET ON TAX AVOIDANCE - Trisandi Eka Putri; Salma Fatin Khairunnisa (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2026)
This study aims to analyze the effect of profitability, leverage, sales growth, and investment opportunity set (IOS) on tax avoidance in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2023–2024 period. The research method applied is quantitative with an associative approach. The data used are secondary data derived from the companies’ annual financial statements. The sample was determined through purposive sampling, resulting in 111 firm-year observations. Multiple linear regression analysis was used to test the hypotheses and determine the relationship between variables. The results show that profitability has a significant positive effect on tax avoidance, leverage has no significant effect on tax avoidance, sales growth has a significant positive effect on tax avoidance, and IOS has no significant effect on tax planning.avoidance. Simultaneously, the four independent variables significantly affect tax avoidance. These findings indicate that a firm’s financial performance, especially profitability, and sales growth, plays a crucial role in shaping managerial decisions related to tax planning and avoidance behaviour.